Idiotype vaccine strategies for treatment of follicular lymphoma. (January 2011) - Mahaseth, Hemchandra; Brody, Joshua D; Sinha, Rajni; Shenoy, Pareen J; Flowers, Christopher R
Follicular lymphoma is an indolent lymphoma associated with a relapsing course. Immunization with tumor B cell idiotype (Id; a unique variable region of surface B cell immunoglobulin) may induce humoral and cellular immune response against the tumor. Based on promising results from early phase clinical trials with Id vaccine, three Phase III trials were initiated, which, despite failing to meet their primary end points, still provided a glimmer of optimism. This article describes the clinical development of the Id vaccine against follicular lymphoma, outlines the outcomes of clinical trials and delineates the future prospects for the integration of the idiotype vaccine into follicular lymphoma treatment.